Leakage Current Analysis on Polymeric Surface Condition using Time-Frequency Distribution - Zainal Abidin, Nur Qamarina; Abdullah, Abdul Rahim; NORDDIN, NURBAHIRAH; Aman, Aminudin; Ibrahim, Khairul Anwar (2012)
Leakage current frequency components are frequently used as a tool for surface condition monitoring on polymeric insulation material and their pollution severity. Fast Fourier Transform (FFT) is one of the methods that are applied for the analysis, but it has some limitation in non-stationary signal. This paper presents analysis of leakage current on polymeric insulation material for high voltage application in frequency domain and time-frequency representation. Tracking and erosion test (Inclined Plane Test (IPT)) complying with BS EN 60587-2007 is conducted on polymeric insulation to select a set of different leakage current patterns from capacitive, resistive and discharge. Then, the leakage current patterns are analysed in frequency domain and time-frequency representation using Fast Fourier Transform and spectrogram technique, respectively. It is found that the surface condition of polymeric insulation material state can be classified accurately by using spectrogram compared to Fast Fourier Transform.